A new genus of the tribe Cotesiini Mason (Hymenoptera: Braconidae: Microgastrinae) from China - Xiong, Yan-Hong; Achterberg, Cornelis Van; Chen, Xue-Xin (Zootaxa, 2017)
A new genus of Microgastrinae (Braconidae) from China is described and illustrated: Eripnopelta Xiong, van Achterberg & Chen, gen. nov. (type species: E. ithyvena Xiong, van Achterberg & Chen, sp. nov. from Zhejiang, Guizhou and Ningxia).